IJCM_173A: A Cross-Sectional study to determine the role of social media influencers and online food delivery platforms as a risk factor for obesity among adults in Rural Perambalur - Christopher Bristly R; Abishek J (Wolters Kluwer Medknow Publications, 2024)
Background: Overweight and obesity are defined as abnormal or excessive fat accumulation that presents a risk to health. Around 2.8 million people dying each year as a result of being overweight or obese. The Time spend on social media and other online platforms has remarkably increased and also the prevalence of Noncommunicable disease. The Food related decisions influenced by social media has detrimental effects on the health. Objectives: 1. To assess the role of social media influencers and online food delivery platforms on BMI among adults of Perambalur 2. To determine the association between social media influencers and online food delivery platforms with obesity Methodology: We conducted a cross-sectional study in 399 adults of Perambalur district from March 2023 - May 2023. Consent was obtained. A Semi-structured self-reported questionnaire was used to collect socio-demographic, second section consist of impact of social media influencers on food consumption and third section consist of questions related to food ordering and online food delivery app usage. The collected data were analyzed using SPSS Version 23. Results: There is a significant association between people who use food delivery apps in higher frequency and obesity. 53.3% of people who are obese have higher frequency of usage of food delivery apps. There is a significant association between usage of social media and obesity. 21.7% of people who are obese have higher usage of social media. Conclusion: The increasing usage of social media and online food delivery platforms has lead to easy access to foods and an increase in prevalence of obesity and other medical complications. So proper recommendations should be made to prevent the younger generations from such diseases.